(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
In this article, factors that directly or indirectly affect emotional stress in adolescents with disabilities, individual psychological characteristics of adolescents and the level of emotional stability are analyzed from a socio-psychological point of view.